Implementation of the Village Financial System Application (SISKEUDES) Version 2.0.2 and the Quality of Village Financial Reports: Implementasi Aplikasi Sistem Keuangan Desa (SISKEUDES) Versi 2.0.2 dan Kualitas Laporan Keuangan Desa - Fauziah, Rina; Biduri, Sarwendah (Indonesian Journal of Innovation Studies, 2021)
This study aims to examine the implementation of the Village Financial System (SISKEUDES) version 2.0.2 and the quality of village financial reports. This study focuses on extracting information, analyzing and understanding the opinions of informants regarding the Implementation of the Village Financial System Application(SISKEUDES) Version 2.0.2 which is a development from the previous version. This study was conducted in Dukuhsari Village, Kupang Village and Kedungcangkring Village. Furthermore, an evaluation of the implementation of the village financial system version 2.0.2 and the quality of financial reports was carried out in these three villages. The Village Financial System Application (SISKEUDES) is an application which used by village government officials, especially in the process of managing and preparing village financial reports. This research uses a qualitative approach. The method used in this research is descriptive method. The sources of data used in this study are primary data sources obtained from the Head of Planning and Head of Finance in three villages, while secondary data sources are obtained from documents of applicable regulations and laws. While the data collection methods that used are observation, interviews, and documentation. Furthermore, the data analysis techniques used are data collection, data reduction, data display, and data verification. The results of the study note that the use of Siskeudes Version A2.0AR.0.1.better in terms of input to administration and book keeping processes, and already integrated with documents at the planning and budgeting stages, compared to Siskeudes Version 1.0.R1.06.